Hana wa sakuragi: Discourse analysis of cherry blossoms in haiku of ‘The Great Four’ - Ramlan, Muhammad Nadzif (Universitas Dian Nuswantoro, 2021)
The proverb hana wa sakuragi, hito wa bushi highlights the significance of cherry blossoms (sakura) as the pinnacle of Japanese aesthetics and floral symbolism. This paper constructed a discourse analysis of cherry blossoms portrayed in the haiku by the Great Four - namely Matsuo Basho, Yosa Buson, Kobayashi Issa and Masaoka Shiki. Three poems from each poet were analyzed as samples, accumulating to 12 haiku overall. To avoid equivocality, all 12 haikus observed would explicitly mention sakura with its kanji character or hiragana. The analysis would cover linguistic aspects and metaphorical interpretations associated to convey the portrayal of cherry blossoms in the context of that haiku. Further discussion of the analysis would have the creative representations of cherry blossoms among the four esteemed poets to be compared in six aspects – time, imagery, state, rhetoric, idiomatic expression and contrasting quality. With both linguistic aspect and relativistic viewpoint to form the discourse analysis, this shows that cherry blossoms can act as a form of display for personal philosophical values and personalities of the four Japanese poets specifically as well as the Japanese society in general.